A brief history of light and those that lit the way - Weiss, Richard J. (Richard Jerome), 1923- (Series in popular science ;, 1996)
From Leonardo to Oppenheimer, from candles to lasers, from cave drawings to cinema, from Stonehenge to quantum mechanics, from Genesis to the Big Bang, light has filled our thoughts, our way of life, our aesthetics, our technology, and our means for survival. Richard Weiss leads us along these paths over the past 500 light years. The way is lit by pioneers such as Rembrandt, Einstein, D W Griffith, Newton, and Heisenberg. A Brief History Of Light, And Those That Lit The Way is a summer's day roller-coaster ride through five centuries of man's achievements in understanding and manipulating ligh.